105k views
0 votes
(yz)log y - logz . (zx)log 2 - log x
- (xv) log x-logy = 1​

1 Answer

5 votes

Answer:

yz)

log(

z

y

)

.(zx)

log(

x

z

)

.(xy)

log(

y

x

)

=

x

log(

x

z

)

.x

log(

y

x

)

×

y

log(

z

y

)

.y

log(

y

x

)

×

z

log(

z

y

)

.z

log(

x

z

)

=x

log(

y

z

)

.y

log(

z

x

)

.z

log(

x

y

)

=(x

logz−logy

).(y

logx−logz

).(z

logy−logx

)

=

x

logy

x

logz

.

y

logz

y

logx

.

z

logx

z

logy

=

y

logx

x

logz

.

z

logy

y

logx

.

x

logz

z

logy

=1

User Rob Conklin
by
5.4k points